Hyperfine Field and Isomer Shift Evolution in Hydrogenated Nd–Fe–B Alloy - Saccone, F. D. (2001)
RE2Fe14B (RE=rare earth) materials are capable of absorbing hydrogen to form a stable solid solution at room temperature. Hydrogenation produces a number of significant changes in the hyperfine interactions. In this work, 57Fe Mössbauer effect spectroscopy and X-ray diffraction measurements were performed on Nd14.01Hf0.08Fe78.91B7.00 alloys submitted to thermal treatment in hydrogen atmosphere. A non-linear increase of the hyperfine fields and isomer shifts with hydrogen concentration was observed. The hyperfine parameters of the 8j1 site exhibit a rather different evolution than those experienced by the other major sites (8j2, 16k1, 16k2). The origin of the hyperfine field enhancement is analyzed in terms of volume expansion and H nearest neighbors to the Fe sites. A linear expression on these two effects to give account of isomer shift evolution for 8j1 site is given.